Right Atrial Septal In Situ Microthrombus: A Potential Novel Cause of Patent Foramen Ovale‐Associated Stroke - Jianbo Zhu; Anni Chen; Lei Zhu; Yun Li; Zhenzhen Jiang; Dijia Ni; Yuanyuan Zheng; Xiatian Liu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Patent foramen ovale (PFO)‐associated stroke has a complex and diverse pathogenesis. It mainly results from a paradoxical embolism caused by venous thrombosis. However, few studies have investigated the presence of an in situ thrombus in the right atrium. Transesophageal echocardiography can effectively detect right atrial septal in situ microthrombus. Therefore, we aimed to explore the relationship between a right atrial septal in situ microthrombus and PFO‐associated stroke and further dissect the pathophysiological basis of microthrombus formation. Methods and Results Between April 2022 and October 2023, we prospectively investigated 466 patients who visited our hospital for transesophageal echocardiography with a high clinical suspicion of PFO. Right atrial septal in situ microthrombus was detected in 34 patients (7%), and 23 of them were examined. The microthrombus disappeared in 13 patients and decreased in 7; PFO recanalization and anatomical variations were observed in 2 and 1 patient, respectively. The incidence of index stroke was higher in the microthrombus group than in the nonmicrothrombus group (76.47% versus 61.11%). Univariate and multivariable (adjusted) analyses revealed PFO as an independent risk factor for right atrial septal in situ microthrombus formation (odds ratio, 3.29 [95% CI, 1.49–7.26]; P=0.003). Conclusions Transesophageal echocardiography effectively detects right atrial septal in situ microthrombus. A PFO may promote the formation of right atrial septal in situ microthrombus. Right atrial septal in situ microthrombus significantly increases the risk of PFO‐associated stroke. This finding may be crucial in disease management strategies for patients with PFO.